Enhancement of Students’ Fitness Using Rhythmic Gymnastics (Batara Gymnastics) - Oktariyana, Oktariyana; Asmawi, Moch; Zamzami, Iman Sulaiman (Department of Physical Education, Sport, Health and Recreation, 2020)
Batara gymnastics is an abbreviation of gymnastic activities that have a fit, agile, and happy character. Batara gymnastics is one of the variations in rhythmic gymnastics created. The purpose of study was to improve students’ body fitness through batara gymnastic for student at eleventh grade SMK Negeri 2 Oku. This research used experimental research. The design of this study used one group pretest posttest design. Process of collecting data used TKJI method. The results of study show that 1) pretest score before doing Gymnastics Batara (Fit Tangkas Gembira) obtained a score of 14.20 while students after doing Gymnastics Batara (Fit Tangkas Gembira) obtained a score of 18.05. Furthermore, the statistical analysis of the T-Test obtained t-count of -10,771 greater than ttable = 1,729. From these results it can be concluded that there is the Effect of Gymnastics Gymnastics (Fit Tangkas Gleeful) on the level of fitness of class XI students in SMK Negeri 2 OKU that is equal to 27.11%.